Flash Glucose Monitoring Improves Glucose Control in People with Type 2 Diabetes Mellitus Receiving Anti-diabetic Drug Medication - Chen, Maoyuan; Li, Huiqin; Shen, Yun; Liu, Bingli; Yan, Renna; Sun, Xiaojuan; Ye, Lei; Lee, Kok-Onn; Ma, Jianhua; Su, Xiaofei (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective To investigate the effects of Flash Glucose Monitoring (FGM) on glucose profile in people with Type 2 Diabetes Mellitus (T2DM) receiving anti-diabetic drug medication.Methods This is a prospective non-randomized uncontrolled study. 111 people with T2DM were enrolled and received FGM for 14 days. There was no change of anti-diabetic medication during the 14 days. The plasma glucose concentration on day 2 was used as baseline and the day 13 was considered as study end point. The parameters to compare were mean plasma glucose (MPG), glucose variations, and incidence of hypoglycemia during the FGM period. The multivariate linear stepwise regression analysis was applied to determine the independent factors that affect MPG difference.Results This study analyzed the data of a total of 111 people with T2DM (male 60 and female 51). The general clinical data of these patients were as follows: age: 65.0±6.7 years old; duration of diabetes: 11.6±6.8 years; HbA1c: 61.2±13.3 mmol/mol; body mass index (BMI): 25.2±3.2 kg/m². Using FGM, people with T2DM were able to change daily diet and exercise through which significant reductions in MPG on days 12 or 13 were achieved as compared with that of day 2 (P=0.04 or P=0.003, respectively). The glucose variations, such as standard deviation (SD) of plasma glucose, coefficient of variation (CV), and mean amplitude of glycemic excursion (MAGE), progressively declined starting from day 6 as compared with baseline (P=0.016, P=0.003, or P=0.012, respectively). The incremental area over the curve (AOC) of the hypoglycemia (<3.9 mmol/L) had a significant reduction starting from the day 3 (P=0.001). When people with T2DM were divided into 3 groups based on the tertile of HbA1c (high, middle, and low concentrations), the reduction of MPG in patients with high concentration of HbA1c were much larger than that in middle and low concentration group patients (P=0.001 for both). The incidence of hypoglycemia was improved in the low concentration group (P=0.017). The optimal frequency of scanning time required to maintain euglycemia was 11.7 times/day as calculated by the receiver operating characteristic (ROC) analysis.Conclusion Using FGM to monitor glucose concentration at 11.7 times/day, people with T2DM can achieve a better glucose control in addition to anti-diabetic drug medication through changing daily diet and exercise, especially in patients with high concentration of HbA1c (>66.1 mmol/mol).
Keywords: flash glucose monitoring; HbA1c; type 2 diabetes mellitus; self-glycemic management